Fire in the heart : how white activists embrace racial justice - Warren, Mark R., 1955- (Oxford : Oxford University Press, 2010)
'Fire in the Heart' presents a study of the processes through which white Americans become activists for racial justice. Warren shows how activists in community organizing, education & criminal justice reform develop a commitment to racial justice and embrace the cause as their own.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Race discrimination -- United States; Racism -- United States; Whites -- United States -- Attitudes; Social action -- United States; United States -- Race relations